Associação de dois analgésicos não evita a sensibilidade causada pelo clareamento dental de consultório: ensaio clínico randomizado, triplo cego. - Alpini, Camila Basso (2018)
Background: Administrating intraoral drugs alone was not able to reduce the TS after bleaching; the objective of this study was to determine if an association of two drugs could induce analgesia at a higher level. Methods: A triple-blind, parallel-randomized clinical trial was conducted with 115 patients receiving either an association of ketorolac tromethamine 10mg /acetaminophen 750mg or a placebo. The first dose was administered 1h before the in-office bleaching, and extra doses every 8h for 48h. The TS was recorded on VAS (0-10) and NRS (0-4) scales, during bleaching and1-6h, 12-18h, 18-24h, 24-48h post-bleaching. The color was measured before and one month after dental bleaching using two visual shade guide and spectrophotometer. The absolute risk of TS was evaluated by Chi-square test. The TS intensity for both scales were compared with ANOVA tests and Mann-Whitney U test. Comparisons between times within each group were performed by the Friedman test. The color changes between groups were compared by the Student t-test (α = 0.05). Results: No significant differences in the absolute risk of TS and color between the groups (p > 0.05), however the intensity of TS decreased in the experimental group for the periods 12 to 24h (p > 0.04) and 24 to 48 h (p > 0.03). Conclusion: The ketorolac tromethamine/acetaminophen association prior to in-office bleaching does not reduce the risk, but reduce the intensity of TS after 12h. Practical Implications: Using two analgesics was capable to prevent TS arising from in-office dental bleaching after 12h.